Portuguese guide lines for the use of biological agents in rheumatoid arthritis - october 2011 update - Fonseca, João Eurico (2017)
The authors present the revised version of the Portuguese Society of Rheumatology (SPR) guidelines for the treatment of Rheumatoid Arthritis (RA) with biological therapies. In these guidelines the criteria for introduction and maintenance of biological agents are discussed as well as the contraindications and procedures in the case of non-responders. Biological treatment (with a tumour necrosis factor antagonist, abatacept or tocilizumab) should be considered in RA patients with a disease activity score 28 (DAS 28) equal to or greater than 3.2 des pite treatment with at least 20mg-weekly-dose of methotrexate (MTX) for at least 3 months or, if such treatment is not possible, after 3 months of other conventional disease modifying drug or combination therapy. A DAS 28 score between 2.6 and 3.2 with a significant functional or radiological deterioration under treatment with conventional regi -mens could also constitute an indication for biological treatment. The treatment goal should be remission or, if that is not achievable, at least a low disease activity, defined by a DAS28 lower than 3.2,without significative functional or radiological worsening. The response criteria, at the end of the first 3 months of treatment, are a decrease of at least 0.6 in the DAS28 score. After 6 months of treatment res ponse criteria is defined as a decrease greater than 1.2 in the DAS28 score. Non-responders, in accordance to the Rheumatologist's clinical opi -nion, should try a switch to another biological agent (tumour necrosis factor antagonist, abatacept, rituxi mab or tocilizumab).